THE INFLUENCE OF SOAKING TEMPERATURE ON THE COEFFICIENT OF DIFFUSION AND PHYSICAL CHARACTERISTICS OF SOYBEAN (Glycine max Merrill) - Pratiwi, Yuanita Kusuma; Waluyo, Sri; -, Warji; ., Tamrin (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2013)
Soybean (Glicine max Merrill)is an important agricultural commodity and very popular in Indonesia as a raw material of such food stuffs for exemple: tempe.  In the producing of tempe, soybean must be submerged in the water.  The soaking process usually is done at room temperature for about 24-48 hours. The longer time of soaking can cause microbial contamination and may affect to the color change, bad taste and moldy smell.  Submersion in warm water is a method that can be used for shortening the soaking time.  The aims of this research were to study the effects of the soaking temperatures on the water diffusion coeffisien and physical characteristics of soybean (moisture content, weigh and dimension).  The research was carried out at 5 levels of soaking temperature:30 °C (as a control), 35 °C, 40 °C, 45 °C, and 50 °C with 3 replications for each treatment. During soaking, sample was taken for measuring its moisture content, dimensional, and weight changes.Temperature history was recorded during soaking. The result showed that there were significant changes ondimension, weight, and water content during soaking. Those parameters increased as the soaking temperaturewas rised. The diffusion coefficient of soybean also increased with rising of soaking temperature. The analysis found that the diffusion coefficients of soybean at temperature of 30 °C, 35 °C, 40 °C, 45 °C, and 50 °C were respectively, 16.4 x 10-11 m2/s; 20.7 x 10-11 m2/s; 38.9 x 10-11 m2/s; 56.3 x 10-11 m2/s and 139 x 10-11 m2/s. The rate of diffusion followed an exponential equation D = 0.058 e0, 1051 / T(R² = 0.960). Keywords: Diffusion coefficient, Soybean, Soaking Temperature, Physical Characteristics